PENERAPAN DISIPLIN KERJA KARYAWAN (STUDI KASUS: CV BANGUN NUSANTARA TEKNIK) - Afifah Nur Vindiarini; Leonard Adrie Manafe (JURNAL ILMIAH EDUNOMIKA, 2022)
This study aims to determine the application of employee work discipline in CV. Bangun Nusantara Teknik (BNT). Analysis of the causes of employee indiscipline problems and ways to solve disciplinary problems that exist in this company. The method used in this study uses a qualitative method. Data collection techniques were carried out by means of interviews and observations. Research informants were taken by purposive sampling, namely five employee representatives who were considered capable of providing explanations related to the research topic. After carrying out the analysis process, the research results could be concluded that BNT employees have a low level of discipline so that it needs to be improved again. Discipline problems faced by this company are employees arriving late at work, high absenteeism that does not enter without any information, delays in doing a job. Leaders are required to increase firmness towards employees, make new rules in writing so that employees could better obey the rules made by the company, and employees should have self-awareness in respecting time in any way if there are new regulations made by the company. Due to with the maintenance of a disciplined attitude, the work will get maximum results.